Impacts of Microplastic Pollution on Soil Ecosystems and Agricultural Productivity - Haseeb Ullah Khan; Abdul Munim; Muhammad Umar Farooq; Nairab Ishaq; Muhammad Ali Waqar (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The pervasive use of plastics has resulted in widespread contamination of agricultural soils by microplastics (MPs, <5 mm). These particles impair crop growth, infiltrate the global food web, and pose a rising threat to agricultural productivity and food security. This review synthesizes data from field surveys and controlled experiments to (1) compare major pathways of MP accumulation—plastic mulching, sewage sludge application, compost amendments, irrigation, and atmospheric deposition; (2) evaluate impacts on soil physicochemical properties; and (3) assess direct effects on seed viability, seedling biomass, plant water uptake, and contaminant transfer. Evidence indicates that MPs may contribute to a projected 5–15% decline in crop yields in the coming decades. However, these effects are dose-dependent, type-specific, and strongly influenced by soil context. Significant research gaps remain, including the lack of standardized detection and quantification protocols, limited long-term and field-scale studies, and inadequate policy and management strategies. Addressing these challenges requires coordinated, interdisciplinary approaches integrating environmental science, agronomy, and policy development. The review concludes by outlining mitigation strategies for MP pollution in agriculture and soil biota, and by identifying priority research directions to clarify poorly understood mechanisms and inform effective interventions.